PRODUKSI BIOKOMPOSIT SEBAGAI DECORATIVE SHEET DARI ECENG GONDOK (EICHHORNIA CRASSIPES) DAN KAYU APU (PISTIA STRATIOTES) HASIL FITOREMEDIASI LIMBAH CAIR INDUSTRI PENYAMAKAN KULIT - Rorezki Gultom, Angela
Environmental pollution by chromium metal waste and organic matter due to the leather tanning industry is one of the water pollution in Indonesia. Phytoremediation is an alternative for remediation of tannery wastewater. Water hyacinth and water lettuce have good ability to absorb organic and inorganic substances and have good resistance to heavy metals. This study aims to evaluate the ability of water hyacinth and Water lettuce wood to remediate leather tanning industry wastewater and utilize their biomass for biocomposite production. At the phytoremediation stage, variations in the concentration of the waste used were 0 (control), 25, and 60%V/V. The results showed that phytoremediation using a combination of water hyacinth and Water lettuce produced the highest percentage reduction in waste variation 60% V/V for total Cr, Cr(VI), NH3, BOD, COD, TDS, and TSS of 91.9%, 91 .45%, 99.94%, 94.53%, 93.02%, 90.28% and 90.63% respectively. Water hyacinth and water lettuce achieved higher Relative Growth Rate (RGR) values for the non-waste variety, namely 0.045 and 0.029. In the manufacture of biocomposites, water hyacinth and water hyacinth stems and leaves which have been dried and chopped up to 100 mesh size are used as fillers in the manufacture of biocomposite. The resulting biocomposite has Ultimate tensile strength (UTS), water absorption, and modulus of elasticity, respectively 0.14 MPa, 77.76%, and 1.13 MPa and when compared with PVC decorative sheet, decorative sheet PVC is still better. The density value is lower than that of PVC decorative sheets and can be decomposed in less than 9 days so that in terms of density and biodegradability the biocomposite is better. Based on these parameters, the biocomposite produced in this study cannot be used as a substitute for PVC decorative sheet.